Evidence for Training-Induced Changes in miRNA Levels in the Skeletal Muscle of Patients With Type 2 Diabetes Mellitus - Simaitis, Sarah; Schulte-Körne, Benedikt; Schiffer, Thorsten; Bloch, Wilhelm; Predel, Hans-Georg; Brixius, Klara; Brinkmann, Christian (Frontiers in Physiology, 2020)
Physical training can improve glycemic control in patients with type 2 diabetes mellitus (T2DM). However, the underlying mechanisms are not entirely clear. An interesting piece of the puzzle could be the regulation of micro-RNAs (miRNAs). They are important modulators of protein expression. Some miRNAs were found to be both linked to poor glycemic control/insulin resistance (with evidence from in vivo and/or in vitro studies) and dysregulated in the skeletal muscle of T2DM patients. This pilot study examines whether a 3-month endurance training program (3 times a week, 70-80% HRpeak) can down-regulate their levels in T2DM men (n=7). One skeletal muscle biopsy sample was obtained from each patient at T1 (6 weeks pre-intervention), one at T2 (1 week pre-intervention) and one at T3 (3-4 days post-intervention). MiRNA-27a-3p, -29a-3p, -29b-3p, -29c-3p, -106b-5p, -135a-5p, -143-3p, -144-3p, -194-5p, and -206 levels were determined by RT-PCR. Friedman ANOVA and post-hoc tests showed that miRNA-29b-3p, -29c-3p and -135a-5p levels were significantly reduced post-training (T3 versus T2 and/or T1). HbA1c and HOMA-IR index did not change significantly. However, HbA1c was reduced in 6 of 7 patients post-training. Furthermore, Spearman’s rank correlation analyses with all values from all time points showed significant negative associations between miRNA-29c-3p, -106b-5p, -144-3p and -194-5p levels and cardiovascular fitness (VO2peak). The study results imply that regular exercise and improving one’s physical fitness is helpful for the regulation of skeletal muscle miRNAs in T2DM patients. Whether or not changes in the miRNA profile can affect the clinical situation of T2DM patients warrants further research.